The pedagogical potential of MMOG: an exploratory study including four games and their players¹ - Gomes, Tiago (2011)
The increasing complexity experienced by electronic games, began to demand a greater cognitive effort from their players. This has fostered some capacities in its players that could be used in teaching and learning. This chapter describes an exploratory study with two phases: the first one analyses four MMOG (Ikariam, OGame, Gladiatus and Metin2) and its pedagogical potential related to the development of problem solving skills, communication and interaction skills, and motivation to perform tasks. The second phase is a survey conducted to the players of these games about their motivation to play and their perceptions about its pedagogical potential. The results showed that all of the four analyzed games are motivating for the players, they have some pedagogical potential related to problem solving, and they improve communication and interaction skills. But the majority of the players felt some difficulties in accepting that they could transfer those developed skills to their scholar or professional life.